CABI Publications 2 Dictionary of natural resource management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Dictionary of natural resource management by Julian and Katherine Dunster 1996 368pp Hbk price UKL4750 ISBN 0 85199 148 3